PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Jeppri Rokky S; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) To identify the role of extension on independent small holder farmers of oil palm; (2) To know empowerment level the farmers; (3) To analyze toward of the aims extension; (4) To analyze influence the role’s of extension toward empowerment the farmers and influence empowerment toward the extension aims. This research was conducted at Bhakti Makmur Village and Lubuk Jawi Village in Bagan Sinembah Sub District Rokan Hilir District. Research’s respondent was determined by purposive sampling methods with number of respondent were 120 respondent’s. The location of the research choosen has active extension activities and has farmer group. Validity, reliability, outliers, normality and multicolinearity analysis has been done on the measuring instruments. Data’s analysis to answer the first, second, and third research purpose scale likert’s summated rating (SLR) was used. And to answer the fourth research purpose structural equation modeling (SEM) with the AMOS program was used. The results shows: (1) The role of extension has shown quite role on independent small holder farmers activity; (2) The level of farmer empowerment is the categorized quite empowerment with the extension activities as seen from empowerment human resource, productive economy, and the farmers institution; (3) The aims of extension has reached as seen from better farming, better business and better living; (4) the role of extension has proven directly influence significantly toward level of farmer’s empowerment and the level of farmer’s empowerment has proven directly influence significantly toward reach of the role extension aims. Key words: The role of extension, empowerments, the role of extension aims, independent small holder, oil palm